MEASURING THE SIXTH SEMESTER STUDENTS’ ENGLISH VOCABULARY AT ENGLISH EDUCATION STUDY PROGRAM OF FKIP UKI TORAJA - Normalia Sirande; Matius Tandikombong; Agustina Pangngala’ (Publikasi dan UKI Press UKI Toraja., 2023)
The problem statement of this research is “how is the sixth-semester students’ English vocabulary size at English education study program of FKIP UKI Toraja”. The objective of this research is to know the sixth-semester students’ English vocabulary size at English education study program of FKIP UKI Toraja. The method used in this research namely the quantitative method. There were 30 students’ of the sixth semester students’ at English education study program of FKIP UKI Toraja which is taken randomly as the participants of this research. The students’ vocabulary size was measured using with Nation VST formula. It is found that the sixth-semester students’ English vocabulary size at English education study program of FKIP UKI Toraja at level 2.000-word level with 10 students’ who passed this level. Only 3 students’ passed the next level 3.000. At level 5.000, only 1 student’ passed. At the university level, only 1 student’ passed this level. No student’ can reach this level 10.000 since it comprises technical terms from different fields of study, and nouns that we rarely meet in our language use. In summary, the sixth-semester students’ English vocabulary at English education study program of FKIP UKI Toraja is still at the high-frequency level, with a vocabulary size of 2,000-word. As a result, individuals are still classified as having a low vocabulary and must enhance their vocabulary by studying the vocabulary of simplified reading books.